Strategies and Challenges in Strengthening Islamic Religious Education for Minority Muslim Students at SD Negeri 091332 Raya Bayu - Saragih, Ahmad Fauzi; Henri, Zulfiana (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract This study examines the challenges and strategies for strengthening Islamic Religious Education (PAI) for minority Muslim students at SDN 091332 Raya Bayu, Simalungun, North Sumatra. PAI plays a crucial role in shaping Islamic understanding, moral values, and spiritual identity, particularly in predominantly non-Muslim environments. This study aims to evaluate the effectiveness of existing educational approaches, identify key obstacles, and explore the application of the fiqh al-aqalliyyat (minority jurisprudence) concept in enhancing Islamic education for minority Muslim students. Employing a descriptive qualitative method, the research involves direct observation and in-depth interviews with the school principal, PAI teachers, and 19 Muslim students. Data were collected through observations, interviews, and document analysis and analyzed using an interactive model. The findings reveal both structural and social challenges in the implementation of PAI. Structurally, the main barriers include limited worship facilities, a lack of contextual teaching materials, and insufficient qualified educators. Socially, Muslim students face difficulties in expressing their religious identity due to social pressures. Community-based approaches, collaboration with religious figures, and the implementation of fiqh al-aqalliyyat have been identified as effective strategies in strengthening Islamic education. This study contributes to academic discourse on Islamic education in minority contexts and offers policy recommendations for a more inclusive approach, such as curriculum revisions and enhanced teacher training. The findings serve as a reference for policymakers and Muslim communities in supporting Islamic education in predominantly non-Muslim settings.   Abstrak: Penelitian ini mengkaji tantangan dan strategi penguatan Pendidikan Agama Islam (PAI) bagi siswa Muslim minoritas di SDN 091332 Raya Bayu, Simalungun, Sumatera Utara. PAI berperan penting dalam membentuk pemahaman Islam, nilai moral, dan identitas spiritual, terutama di lingkungan mayoritas non-Muslim. Studi ini bertujuan mengevaluasi efektivitas pendekatan pendidikan yang ada, mengidentifikasi kendala utama, dan mengeksplorasi penerapan konsep fiqh al-aqalliyyat (fikih minoritas) dalam memperkuat pendidikan Islam bagi siswa Muslim minoritas. Penelitian ini menggunakan metode kualitatif deskriptif dengan observasi langsung dan wawancara mendalam terhadap kepala sekolah, guru PAI, dan 19 siswa Muslim. Data dikumpulkan melalui observasi, wawancara, dan analisis dokumen, kemudian dianalisis menggunakan model interaktif. Hasil penelitian menunjukkan tantangan struktural dan sosial dalam implementasi PAI. Secara struktural, keterbatasan fasilitas ibadah, bahan ajar kontekstual, dan tenaga pendidik menjadi hambatan utama. Secara sosial, siswa Muslim mengalami kesulitan mengekspresikan identitas keagamaannya karena tekanan sosial. Pendekatan berbasis komunitas, kolaborasi dengan tokoh agama, dan penerapan fiqh al-aqalliyyat ditemukan sebagai strategi yang efektif dalam memperkuat pendidikan Islam. Penelitian ini berkontribusi pada kajian akademik tentang pendidikan Islam dalam konteks minoritas dan menawarkan rekomendasi kebijakan yang lebih inklusif, seperti revisi kurikulum dan peningkatan pelatihan guru. Hasil penelitian dapat menjadi referensi bagi pemangku kebijakan dan komunitas Muslim dalam mendukung pendidikan Islam di lingkungan mayoritas non-Muslim.